Coronary Artery Bypass Graft Surgery Using the Radial Artery as a Secondary Conduit Improves Patient Survival. Issue 4 (22nd August 2013) - Lin, John; Cheng, Wen; Czer, Lawrence S.; De Robertis, Michele A.; Mirocha, James; Ruzza, Andrea; Kass, Robert M.; Khoynezhad, Ali; Ramzy, Danny; Esmailian, Fardad; Trento, Alfredo
Abstract : Background: The clinical benefits of the left internal thoracic artery–to–left anterior descending coronary artery graft are well established in coronary artery bypass graft surgery (CABG). However, limited data are available regarding the long‐term outcome of the radial artery (RA) as a secondary conduit over the established standard of the saphenous venous graft. Methods and Results: We compared the 12‐year survival outcome in a set of propensity‐matched CABG patients who received either the RA or the saphenous vein as a secondary conduit. A multivariable logistic regression that included 18 baseline characteristics was used to define the propensity of receiving an RA graft. The propensity model resulted in 260 matched pairs who underwent first‐time isolated CABG from 1996 to 2001 with similar preoperative characteristics (C statistic=0.86). The cumulative 12‐year survival estimated by use of the Kaplan–Meier method was higher for the RA graft patients (hazard ratio 0.76; P =0.03). This survival advantage was especially significant in diabetics ( P =0.005), in women ( P =0.02), and in the elderly ( P =0.04.) The protective effect appeared beginning at year 5 post surgical intervention. Conclusion: The RA as a secondary conduit provided superior long‐term survival after CABG, especially in diabetic patients, women, and the elderly. This effect was most pronounced >5 years after surgery.